Identification of Bacteria Associated in the Small Intestine of White-Tailed Forest Rat (Maxomys hellwandii) in South Minahasa Regency, North Sulawesi - Megawati Meylin Weken; Revolson Alexius Mege; Helen Joan Lawalata; Yermia Semuel Mokosuli; Iriani Setyawati (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Sulawesi Island in the Wallaceae line area has diverse endemic animals, including the white-tailed forest rats. White-tailed forest rat (Maxomys hellwandii) is one of the endemic animals in North Sulawesi, so this study aimed to determine the type of bacterial genus in the small intestine of Maxomys hellwandii. This research used a laboratory-based qualitative descriptive method using a pour plate isolation method and bacterial identification based on morphological, and physiological characters with biochemical tests. The small intestines of Maxomys hellwandii taken from the South Minahasa forest area, North Sulawesi were used as samples of this research. The results of the study obtained 22 isolates of bacteria that were successfully isolated and have been identified based on morphological characteristics, and physiology with biochemical tests based on the book Bergey's Manual of Systematic Bacteriology suspected 14 isolates as genus Bacillus and 8 isolates as genus Lactobacillus.